Analysis of the calcium hydroxide removal of bovine root canals with different techniques by scanning electron microscopy - Mateus Alves Bastos; Flávia Emi Razera Baldasso (Faculdade Meridional IMED, 2019)
Objective: To evaluate the effectiveness of calcium hydroxide removal by comparing manual files, Easy Clean and passive ultrasonic irrigation (PUI) on Ca(OH)2 removal. Method: Thirty bovine incisors teeth wereused in this study. The root canals were prepared and the samples were randomly divided into 3 groups according to the technique used for Ca(OH)2 removal (n = 10): G1: manual files; G2: Easy Clean file; G3: Passive ultrasonic irrigation. After fifteen days, specimens were sectioned and processed for observation of the middle and apical thirds by using scanning electron microscopy (SEM). One blinded and calibrated evaluator attributed scores to each specimen. The data obtained from the SEM analysis were submitted to the Kruskal-Wallys test, followed by the Dunn test. Results: There was no significant difference in Ca(OH)2 removal between manual file and Easy Clean and between Easy Clean and PUI. PUI technique significantly removed more calcium hydroxide when compared with manual file group. None of the tested techniques completely removed the Ca(OH)2 from the root canal walls. Conclusion: Regardless of the technique used, none of the protocols tested completely removed the Ca(OH)2 from the root canal. However, passive ultrasonic irrigation was more effective than manual file group.